2009
DOI: 10.1128/aem.00241-09
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Responses of the Late Blight Pathogen Phytophthora infestans to Cyclic Lipopeptide Surfactants and Their Dependence on G Proteins

Abstract: Oomycete pathogens cause major yield losses for many crop plants, and their control depends heavily on agrochemicals. Cyclic lipopeptides (CLPs) were recently discovered as a new class of natural compounds with strong activities against oomycetes. The CLP massetolide A (Mass A), produced by Pseudomonas fluorescens, has zoosporicidal activity, induces systemic resistance, and reduces late blight in tomato. To gain further insight into the modes of action of CLPs, the effects of Mass A on pore formation, mycelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
2
24
2
Order By: Relevance
“…This is in agreement with the results obtained in our study, in which a high concentration of biosurfactant was needed to affect growth of the mycelium. In contrast to findings reported by Van de Mortel et al (2009), no effect of biosurfactant on sporulation of P. infestans was observed in our study, despite reduced mycelia growth being recorded at the highest biosurfactant concentration. In our study, inhibition of the growth of the mycelium on Petri dishes amended with the highest biosurfactant concentration decreased over time.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…This is in agreement with the results obtained in our study, in which a high concentration of biosurfactant was needed to affect growth of the mycelium. In contrast to findings reported by Van de Mortel et al (2009), no effect of biosurfactant on sporulation of P. infestans was observed in our study, despite reduced mycelia growth being recorded at the highest biosurfactant concentration. In our study, inhibition of the growth of the mycelium on Petri dishes amended with the highest biosurfactant concentration decreased over time.…”
Section: Discussioncontrasting
confidence: 86%
“…In the study by Van de Mortel et al (2009) it was reported that zoospores of P. infestans were most sensitive to the biosurfactant, followed by mycelium and cysts. This is in agreement with the results obtained in our study, in which a high concentration of biosurfactant was needed to affect growth of the mycelium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The deformities observed were similar to those reported earlier, caused due to formation of pores by interaction of biomolecules with the fungal cell membrane resulting in shrunken and empty hyphae (Romero et al, 2007;Makovitzki et al, 2007). The formation of pores further causes an increased Ca 2+ influx which has been reported to induce excessive branching of hyphae (Thrane et al, 1999;Mortel et al, 2009). The appearance of bulbous morphology may also be attributed to the effect of APB on the cytoskeletal elements, actin and tubulin leading to collapsed cytoskeleton and un-polarized growth at the tip of hyphae (Tendulkar et al, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…SS101 was originally isolated from the wheat (Triticum aestivum) rhizosphere (De Souza et al, 2003) and produces massetolide A, a cyclic lipopeptide surfactant with diverse natural functions, including a role in swarming motility, biofilm formation, and defense against protozoan predators (de Bruijn et al, 2008;Mazzola et al, 2009;Raaijmakers et al, 2010). Massetolide A has destructive effects on zoospores of multiple oomycete plant pathogens (De Souza et al, 2003;de Bruijn et al, 2008;van de Mortel et al, 2009) and induces systemic resistance in tomato (Solanum lycopersicum) leaves against Phytophthora infestans (Tran et al, 2007). Here, we show that the resistance response induced by Pf.SS101 in Arabidopsis against the bacterial pathogen Pseudomonas syringae pv tomato (Pst) is mediated by SA signaling and NPR1 but not by JA/ ET signaling.…”
mentioning
confidence: 99%